Pembendaharaan Kata Peserta Didik yang di Pengaruhi oleh Media Sosial di MI Hasyim As’ari Kelas 5 C - Syauqiatul Latifah; Ilmi Amalia Maghfiroh; Esa Nur Faizah (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
The development of digital technology has made social media an integral part of children's lives, including students of Madrasah Ibtidaiyah (MI). This study aims to explore the impact of social media on the language patterns of class 5C students at MI Hasyim Asy'ari. Using a qualitative method with a case study approach, data were obtained through semi-structured interviews and participant observations of 14 students who regularly access social media. The findings show that platforms such as TikTok, Instagram, and YouTube are the main sources of new vocabulary acquisition, such as the terms "kepo", "narsis", and "anjir". These words reflect changes in students' language styles that are increasingly informal and often deviate from standard Indonesian language rules. Although social media can contribute to enriching vocabulary and increasing children's interest in communicating, negative impacts such as the dominance of slang, misuse of meaning, and reduced concern for the correct use of Indonesian are also very real. Therefore, the role of educators and parents in supervising and directing the use of social media is very important. The language learning curriculum in schools needs to be adjusted to the development of the digital era without abandoning appropriate linguistic values. With the right strategy, social media can be used as a useful language learning tool without reducing the essence of Indonesian as a national identity.